Model Matematis Kenaikan Suhu pada Butiran selama Pengepresan pada Pembuatan Tablet Effervescen Buah Markisa - Ansar Ansar; Sirajuddin Sirajuddin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The objective of this research was proposing mathematical models to predict the temperature increasing in the spherical form particles during compression on processing of the passion fruit effervescent tablet. The materials used in this research were passion fruit granule. The data of temperature increase on the materials during compression was recorded by the thermocouple. Result of the research was showed the temperature increase will be distributed by conduction to all position in the particle that can predict with the diffusion equation for dimensions three spherical coordinate. The temperature at the particle surface where friction among the contact points of the particle occurred was higher than Tg of materials of the effervescent tablet component. The particles temperature average increase during compression is 33.03oC.ABSTRAKTujuan penelitian ini adalah membuat model matematis untuk memprediksi kenaikan suhu pada butiran yang dianggap berbentuk bola selama pengepresan pada pembuatan tablet effervescen buah markisa. Bahan yang digunakan dalam penelitian ini adalah granula markisa. Data kenaikan suhu pada bahan selama pengepresan diukur dengan termokopel. Hasil penelitian menunjukkan bahwa kenaikan suhu di permukaan butiran terdistribusi secara konduksi ke seluruh bagian butiran yang dapat didekati dengan persamaan difusivitas panas koordinat bola 3 dimensi. Suhu di permukaan butiran tempat terjadinya gesekan antar titik singgung butiran jauh lebih tinggi dibandingkan dengan suhu Tg bahan komponen penyusun tablet effervescen. Kenaikan rerata suhu butiran selama pengepresan adalah 33,03oC.